Can autonomy make bicycle-sharing systems more sustainable? An environmental impact analysis. (December 2022) - Coretti Sanchez, Naroa; Alonso Pastor, Luis; Larson, Kent
Abstract: Autonomous bicycles have recently been proposed as a new and more efficient approach to bicycle-sharing systems (BSS), but their environmental impacts remain unresearched. Conducting environmental impact assessments at an early technological stage is critical to influencing the design and, ultimately, environmental impacts of a system. Consequently, this paper aims to assess the environmental impact of autonomous shared bikes compared with current station-based and dockless systems under different sets of modeling hypotheses and mode-shift scenarios. The results indicate that autonomy could reduce the environmental impact per passenger kilometer traveled of current station-based and dockless BSS by 33.1 % and 58.0 %. The sensitivity analysis shows that the environmental impact of autonomous shared bicycles will mainly depend on vehicle usage rates and the need for infrastructure. Finally, this study highlights the importance of targeting the mode replacement from more polluting modes, especially as traditional mobility modes decarbonize and become more efficient. Highlights: Autonomous bicycles have been proposed as a new approach to bicycle sharing systems. The impacts of new mobility modes should be assessed at an early technology stage. Autonomy could reduce the environmental impact of current bicycle-sharing systems. Vehicle utilization and infrastructure needs will have the most significant impact. As other vehicles decarbonize the mode-shift should focus on the most polluting modes.